Subclinical Left Ventricular Systolic Dysfunction in Patients with Septic Shock Based on Sepsis-3 Definition: A Speckle-Tracking Echocardiography Study - Pham Dang Hai; Le Lan Phuong; Nguyen Manh Dung; Le Thi Viet Hoa; Do Van Quyen; Nguyen Xuan Chinh; Vu Duy Minh; Pham Nguyen Son (Critical Care Research and Practice)
Introduction. Left ventricular dysfunction is quite common in septic shock. Speckle-tracking echocardiography (STE) is a novel, highly sensitive method for assessing left ventricular function, capable of detecting subclinical myocardial dysfunction, which is not identified with conventional echocardiography. We sought to evaluate subclinical left ventricular systolic function in patients with septic shock using speckle-tracking echocardiography. Methods. From May 2017 to December 2018, patients aged ≥18 years admitted to the intensive care unit with the diagnosis of sepsis and septic shock based on the sepsis-3 definition were included. Patients with other causes of cardiac dysfunction were excluded. Transthoracic echocardiography was performed for all the patients within 24 hours of diagnosis. Left ventricular systolic function was assessed using conventional echocardiography and speckle-tracking echocardiography. Results. Patients with septic shock (n = 90) (study group) and 37 matched patients with sepsis but no septic shock (control group) were included. Left ventricular ejection fraction (LVEF) by conventional echocardiography showed no significant difference between two groups (58.2 ± 9.9 vs. 58.6 ± 8.3, p=0.804). The global longitudinal strain (GLS) by STE was significantly reduced in patients with septic shock compared with that in the control (−14.6 ± 3.3 vs. −17.1 ± 3.3, p<0.001). Based on the cutoff value of GLS ≥ −15% for the definition of subclinical left ventricular systolic dysfunction, this dysfunction was detected in 50 patients with septic shock (55.6%) and in 6 patients in the control group (16.2%) (p<0.05). Conclusions. Speckle-tracking echocardiography can detect early subclinical left ventricular systolic dysfunction via the left ventricular global longitudinal strain compared with conventional echocardiographic parameters in patients with septic shock.